Influence of Gd3+ co-doping on structural property of CaMoO 4:Eu nanoparticles - Singh B.P.; Parchur A.K.; Ningthoujam R.S.; Ansari A.A.; Singh P.; Rai S.B. (My University, 2025)
A facile auto-combustion route is used for the synthesis of Gd3+ (2, 5, 7 and 10 at%) co-doped CaMoO4:Eu nanoparticles. X-ray diffraction study suggests that as-prepared samples have extra impurity phases in addition to main tetragonal phase of CaMoO4, and such extra phases decrease as the annealing temperature increases from 600 to 900 °C. The crystal structure has been analysed using Rietveld program. It has space group I41/a (88) and Z = 4 (number of CaMoO4 formula units per unit cell). Average crystallite sizes of as-prepared, 600 and 900°C annealed samples for 2 at% Gd3+ are found to be ∼33, 48 and 61 nm, respectively. The lattice strains of 5 at% Gd3+ co-doped CaMoO 4:Eu for as-prepared and 900°C are 0.001 and 0.002, respectively. Fourier transform infrared spectroscopy gives the absorption bands at ∼815 and 427 cm-1, which are related to asymmetric stretching and bending vibrations of MoO42- tetrahedron. Particle morphology is studied using scanning and transmission electron microscopy (SEM and TEM), and aggregation of particles is found. X-ray photoelectron spectroscopy (XPS) is utilized to examine the oxidation states of metal ions/oxygen and oxygen ion vacancies in Gd3+ co-doped CaMoO4:Eu. With an increase in Gd3+ concentration, peaks corresponding to the Gd3+ (2p3/2 and 2p5/2) binding energy could be detected. © 2014 The Royal Society of Chemistry.